Improvement strategies for the oral bioavailability of poorly water-soluble flavonoids: An overview - Zhao, Juanjuan; Yang, Jun; Xie, Yan (International journal of pharmaceutics, 2019)
[Display omitted] Although flavonoid compounds have various pharmacological applications, they generally exhibit low oral bioavailability due to their poor aqueous solubility. To address this problem, numerous promising strategies, such as the use of an absorption enhancer, structural transformation (e.g., prodrugs, glycosylation), and pharmaceutical technologies (e.g., carrier complexes, nanotechnology, cocrystals), have been developed and applied to deliver poorly water-soluble flavonoids. These formulation approaches can effectively improve the oral bioavailability of flavonoids by enhancing their solubility, dissolution rate and permeability; preventing their degradation or metabolism in the gastrointestinal tract; and/or delivering them directly to their physiological targets. This review comprehensively summarizes the viable oral delivery systems for insoluble flavonoids to date and discusses their design principles, potential advantages, possible limitations, and oral delivery efficiency, which will provide some useful clues and references to overcome the absorption barrier of these insoluble flavonoids.